2007
DOI: 10.1159/000107695
|View full text |Cite
|
Sign up to set email alerts
|

Implants of Estradiol Conjugated to Bovine Serum Albumin in the Male Rat Medial Preoptic Area Promote Copulatory Behavior

Abstract: The expression of mating behavior in male rats is dependent on estrogen-responsive neurons in the medial preoptic area (MPO). Previous reports showed that mating is attenuated if the aromatization of testosterone to estradiol (E2) is blocked in the MPO and that mating is maintained by MPO E2 implants. However, the mechanisms by which E2 exerts its action are not fully understood. It had been thought that E2 acted exclusively by binding to nuclear estrogen receptors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 133 publications
0
11
0
Order By: Relevance
“…In contrast, stimulation of the POA increases copulation in male mice (44), and the expression of c-Fos in the POA is increased in male mice (43,45,46). Within the POA, implants of estradiol promote sexual behaviors in male mice (22,47,48). In female mice, lesions of the POA decrease proceptivity and increase receptivity in female mice, whereas electrical stimulation of the MPA led to persistent decreases in lordosis (49,50) without interfering with proceptivity (50).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, stimulation of the POA increases copulation in male mice (44), and the expression of c-Fos in the POA is increased in male mice (43,45,46). Within the POA, implants of estradiol promote sexual behaviors in male mice (22,47,48). In female mice, lesions of the POA decrease proceptivity and increase receptivity in female mice, whereas electrical stimulation of the MPA led to persistent decreases in lordosis (49,50) without interfering with proceptivity (50).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the idea that some genomic priming is required to observe rapid effects of estrogens on male sexual behavior [56; 264], these results suggest that the acute control of male sexual behavior by estrogens likely involves an integration of non-genomic and genomic processes depending on ERα, at least in part. Interestingly, copulatory behavior was facilitated within 48h after the bilateral implantation of E 2 -BSA in the medial preoptic area (MPOA) of castrated male rats chronically treated with the androgenic metabolite of testosterone, dihydrotestosterone (DHT; [119]). This observation first suggested that estrogen membrane signaling was involved in the control of male sexual behavior.…”
Section: Membrane Estrogen Receptors and Male Physiology And Behaviormentioning
confidence: 99%
“…Inhibition of testosterone conversion to oestrogen by infusion of the aromatase inhibitor, fadrozole, into the MPOA of gonadally intact male rats decreased sex behaviours (49), and sex behaviours were restored with MPOA implants of oestrogen and oestrogen-BSA conjugate, suggesting that non-genomic mechanisms mediated oestrogen action (50). Thus, both AR and ER in the MPOA are critical for the expression of male sexual behaviour.…”
Section: Sexual Behaviour and Androgen Receptorsmentioning
confidence: 99%